Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la Carrera de Educación Básica de la Facultad de Educación, el Arte y la Comunicación, 2023-2024. - Juca Rivera, Tania Michelle (2024)
The curricular integration work aimed to analyze the relationship between the basic cognitive processes of attention and memory and reading comprehension in first-cycle students of the Faculty of Education, Art and Communication Basic Education career, 2023-2024. The research adopted a quantitative, descriptive, correlational, cross-sectional approach, with a non- experimental design and a sample of 33 students; the instruments used were the d2 test for attention, the RIAS subscale for memory and the ICLAU instrument to evaluate reading comprehension. It was employed Kendall's Tau-b coefficient to establish the correlations, interpreted according to Pearson's correlation coefficient scale. The results revealed that 69.70% of the students showed a low attention level, 3.03% a medium level and 27.27% a high level. Regarding memory, 33.33% had a low level, 42.42% a medium level and 24.24% a high level. Regarding reading comprehension, 30.30% had a low level, 39.4% a medium level and 30.30% a high level. The correlation between attention and reading comprehension, measured with Kendall's correlation coefficient of 0.327, revealed a medium positive correlation according to Pearson's correlation coefficient. Similarly, the correlation between memory and reading comprehension of 0.426 also indicated an average positive correlation, these results accept the alternative hypothesis of the research, confirming the relationship between the variables studied.